Arte Italiana 1960-1982. - Aghina, Guido; Ballo, Guido; Barilli, Renato; Caroli, Flavio; Dempsey, Andrew; Drew, Joanna; Fagone, Vittorio; Giaccari, Luciano; Parmesani, Loredana; Sanesi, Roberto; Tisdall, Caroline; Tognoli, Carlo; et al. (London : Arts Council of Great Britain, 1982)
Accame, Vincenzo ; Adami, Valerio ; Agnetti, Vincenzo ; Aricó, Rodolfo ; Ascari, Ferruccio ; Baj, Enrico ; Bartolini, Luciano ; Battaglia, Carlo ; Bentivoglio, Mirella ; Berardinone, Valentino ; Biasi, Alberto ; Boetti, Alighiero ; Bonalumi, Agostino ; Boriani, Davide ; Bosco, Dal ; Carpi, Cioni ; Carrega, Ugo ; Carrino, Nicola ; Cavaliere, Alik ; Ceroli, Mario ; Chiari, Giuseppe ; Cintoli, Claudio ; Cividin, Luisa ; Clemente, Francesco ; Coletta, Pietro ; Colombo, Gianni ; Consagra, Pietro ; Dadamaino ; Devalle, Beppe ; Falso Movimento ; Ferrari, Vincenzo ; De Filippi, Fernando ; Fioroni, Giosetta ; Fonosfera ; Fontana, Lucio ; Galliani, Omar ; Gastini, Marco ; Gianikian ; Granchi, Andrea ; Griffa, Giorgio ; Gruppo T ; Isgrò, Emilio ; Jori, Marcello ; Kounellis, Jannis ; Lora-Totino, Arrigo ; Lucchi, Ricci ; Mainolfi, Luigi ; Manai, Piero ; Manzoni, Piero ; Maraniello, Giuseppe ; Mari, Enzo ; Martelli, Plinio ; Matino, Vittorio ; Mattiacci, Eliseo ; Merz, Mario ; Miccini, Eugenio ; Mochetti, Maurizio ; Mussio, Magdalu ; Nanni, Mario ; Nespolo, Ugo ; Notargiacomo, Gianfranco ; Novelli, Gastone ; Oberto, Anna ; Oberto, Martino ; Olivieri, Claudio ; Ontani, Luigi ; Paladino, Mimmo ; Paolini, Giulio ; Paradiso, Antonio ; Pardi, Gianfranco ; Pascali, Pino ; Patella, Luca Maria ; Pezzo, Lucio Del ; Pietra, Ugo La ; Pignotti, Lamberto ; Pisani, Vettor ; Pistoletto, Michelangelo ; Plessi, Fabrizio ; Pomodoro, Arnaldo ; Pomodoro, Gio ; Pozzati, Concetto ; Romagnoni, Bepi ; Rotella, Mimmo ; Salvo ; Sambin, Michele ; Savio, Francesco Lo ; Schifano, Mario ; Scienza, Gaia ; Simonetti, Gianni Emilio ; Spagnulo, Giuseppe ; Spatola, Adriano ; Spoldi, Aldo ; Staccioli, Mauro ; Syxty, Antonio ; Tadini, Emilio ; Tancredi ; Taroni, Roberto ; Uncini, Giuseppe ; Vaccari, Franco ; etc.
biografie
Arte Italiana 1960-1982, Hayward Gallery, London, 20 October 1982 to 9 January 1983 ; Institute of Contemporary Arts, London, 12 to 24 October 1982
Engels
boek
Keywords: Italië